PREDICAMENTS OF STATE BUILDING UNDER EXLIBERATION MOVEMENTS: MAKING SENSE OF THE CURRENT CRISIS IN SOUTH SUDAN - Kalewongel Minale (European Scientific Journal, ESJ, 2014)
The tenacity and strength of guerilla movements to wage a protracted armed struggle is almost an empirically proven fact. In Africa and the entire world, there are several instances of guerrilla movements that fought with resilience, strong courage, heroism and an incredible sense of devotion and commitment. However, once they capture political power and preside over the state, the record of these movements in the (re) building of legitimate, democratic and sustainably peaceful states has largely been disappointing. The objective of this study is to shed light up on the challenges of state building in the background of the current crisis in South Sudan. Based on the analysis of primary and secondary data, it argues that the ongoing crisis (civil war) in South Sudan is part of a broader and a recurrent problem of state building under the tutelage of ex- liberation movements; and hence its solutions should be sought in the overall transformation of the SPLM/A into a viable political party.